2016
DOI: 10.4055/jkoa.2016.51.5.443
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Traumatic Radial Head Anterior Dislocation Treated with Open Reduction in Children

Abstract: Isolated traumatic radial head anterior dislocation without associated injuries is uncommon in pediatric patients. If diagnosed on time, most cases can be reduced by closed reduction. In some cases, the radial head was found to be trapped between annular ligament, anterior joint capsule and a buttonhole tear of the brachialis muscle, preventing closed reduction. This is a very uncommon injury and the diagnosis can be overlooked. We report a case of a 7-year-old girl who sustained an irreducible isolated disloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Takase and Mizuochi 20 , Bradley et al 21 ,. and Chung et al 36 . reported cases treated successfully with open reduction, and their patients came for surgery 1 day, 3 days, and 30 days after the initial trauma, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takase and Mizuochi 20 , Bradley et al 21 ,. and Chung et al 36 . reported cases treated successfully with open reduction, and their patients came for surgery 1 day, 3 days, and 30 days after the initial trauma, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining case was 62 days after injury, and was carried out with ulnar osteotomy. Takase and Mizuochi 20 , Bradley et al 21 , and Chung et al 36 reported cases treated successfully with open reduction, and their patients came for surgery 1 day, 3 days, and 30 days after the initial trauma, respectively. Gupta et al 37 performed an open reduction of the radial head and reconstruction of the annular ligament on cases with a duration of delayed diagnosis of 6 weeks and 3 months.…”
Section: Discussionmentioning
confidence: 99%